PENINGKATAN KAPASITAS PENGELOLAAN KEUANGAN UMKM MELALUI IMPLEMENTASI AKUNTANSI SEDERHANA - Tuti setiatin; Ebah Suaebah; Muhammad Zaky (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as a strategic backbone for Indonesia’s national economy; however, they frequently face structural challenges, most notably low financial management capacity and literacy,. Many MSME owners lack systematic bookkeeping practices and often conflate personal and business finances, which subsequently restricts their access to formal financing and hinders business sustainability. This community service initiative aims to strengthen MSME financial management capacity through the implementation of simplified and practical accounting methods. The program utilized a systematic and participatory methodology, conducted on January 24, 2026, which included three primary phases: preparation (needs identification), implementation (interactive training, discussions, and simulations), and evaluation (pre-test and post-test assessments). Results indicate a significant improvement in both the theoretical knowledge and practical skills of participants, particularly regarding daily transaction recording, the preparation of simplified profit and loss statements, and the segregation of business and personal cash flows. Despite challenges such as varying levels of participant comprehension and limited training time, the program proved effective in enhancing financial literacy,. In conclusion, the implementation of simplified accounting empowers MSMEs to accurately monitor their financial health, thereby supporting informed decision-making and long-term business competitiveness. To ensure the permanence of these improvements, continuous mentoring and periodic assistance are recommended.